HER2 Reactivity Pattern and Association with Various Tumor Factors in Breast Cancer Patients - Greeshma Ann George; Philips Antony (International Journal of Integrated Health Sciences, 2025)
Background: Breast cancer prognosis and therapeutic strategies are strongly influenced by biomarker profiles, particularly HER2 reactivity, which impacts treatment selection and disease progression.